The information role of advisors in mergers and acquisitions: Evidence from acquirers hiring targets’ ex-advisors - Chang, Xin; Shekhar, Chander; Tam, Lewis H.K.; Yao, Jiaquan (Journal of Banking & Finance, 2016)
We examine the information role of financial advisors by focusing on mergers and acquisitions in which acquiring firms hire target firms’ ex-advisors. We document that by employing targets’ ex-advisors, acquirers pay lower takeover premiums and secure a larger proportion of merger synergies. The corresponding targets exhibit lower announcement returns and are less likely to be propositioned by competing bidders. These results indicate that acquirers take advantage of value-relevant information about targets through targets’ ex-advisors, and achieve bargaining advantages in deal negotiations. In contrast, we document no discernible value effects when targets hire acquirers’ ex-advisors, suggesting that the information role of acquirers’ ex-advisors hired by targets is weaker than that of targets’ ex-advisors hired by acquirers.